Satisfation and service quality in public and private organizations Lima Metropolitan - Loli Pineda, Alejandro (2013)
The present exploratory research has as an objective to know the relationship between the customer satisfaction and the service quality in public and private organizations in Lima Metroplitana, and the way how is related to some demographic, social, and organizational variables in a sample of 174 individuals, who attend to the pointed out organizations as users to buy general goods and services. The analyisis of the results takes us to confirm that most of the sample participants show a favorurable opinion regarding to the quality of the service. By the same token, most of the individuals show satisfation regarding to the quality of the service. On the other hand, the correlation between the satisfaction and the quality service shows a significative and psoitive. About the demographic, social, and organizational variables and their relation to the satisfaction and the quality of the service; it can be seen that there is a difference significative, even though moderate; in the first case, with the gender, and in the second case, there is no relationship to any of the other variables, in other words, the intervention of those variables do not allow to infer differences about user perceptions about the satisfaction users, and the quality of the goods and services that are offered by the organizations, except the variable gender.